Harmonic kicker cavity for high power operation - Park, Gunn Tae; Guo, Jiquan; Marchlik, Mattew; Rimmer, Robert A.; Overstreet, Sarah; Wang, Haipeng (Physical review. Accelerators and beams, 2023)
A harmonic kicker cavity was originally proposed as an ultrafast bunch exchange device between energy recovery linac (ERL) and the circulator cooling ring (CCR) of the Jefferson Laboratory Electron-Ion Collider (JLEIC). The cavity is a transverse deflecting cavity that delivers a sharp kick synthesized using a linear combination of harmonic modes, which can be developed as a normal conducting quarter wave resonator (QWR). We present the development of the QWR as a high-power device (up to 7.5 kW) ready for a beam test: rf design (that involves the rf power optimization, tuning mechanism of five harmonic modes, power coupling), multipacting study, mechanical design with a water cooling system for high power operation, fabrication, and the rf bench tests.